THE OBJECTIVES OF TAKAFUL AND SHARIAH: TOWARDS THE ACHIEVEMENT OF MAQASID SHARIAH - Abdullah, Syahida (Journal of Human Capital Development (JHCD), 2015)
Takaful is a fast growing industry that has great market potential. It is largely due to the shariah principles embedded in it that emphasizes on the values of mutual help, brotherhood and shared responsibility with elimination of shariah prohibited elements such as interest (riba), excessive uncertainty (gharar), and gambling (maysir) in its business operation and in all its activities. These prohibited elements exist in conventional insurance which makes it obviously different from takaful. The objectives of takaful are seen to be in consistent with the objectives of shariah that aim to provide benefit and protection to the Ummah. The comprehensiveness of shariah objectives in takaful practices includes the perseverance of five fundamental elements in human’s life that are: ad-din (religion), an-nafs (life), al-‘aql (intellect), an-nasl (ancestry) and al-mal (property or wealth). The paper thus concludes by recognizing the importance of the relationship between shariah objectives and takaful objectives towards capturing greatertakaful market share. Keywords: takaful, maqasid shariah, wealth, mutual assistance, brotherhood and shared responsibility